AN [UN]MAKING OF THE WORLD:1 A POSTCOLONIALIST RESPONSE TO TRANSFORMATIVE CONSTITUTIONALISM (The Pretoria Student Law Review, 2021)
In this paper we critically engage with transformative constitutionalism as a project of imagination and a response to disenchantment. Drawing on post-colonialist feminist conceptions of the law, we explore the promise of the ‘legal imagination’ and its ability to re-enchant our understanding of equality and redefine universal standards employed by the law. The critique of disenchantment is two-fold. First, the formal application of rules mandated by the law allows for the absence of thought and by extension, the absence of judgement. Hannah Arendt understands the employment of ‘pure’ scientific knowledge as possessing the means to destroy the world. Similarly, a legal tradition founded on formalism possesses the means to destroy the society it claims to protect. Second, the law’s commitment to disenchantment has entrenched a universal standard that privileges the masculine and disparages the feminine ‘other’. Indeed Drucilla Cornell argues that no known society has successfully escaped ‘symbolic traces of an ideological masculinity’. In a postcolonial context disenchantment is further entrenched by the colonial relationship that serves to marginalise all that is in conflict with the western universal. Reference will be made to Hélène Cixous’ work on dualist thinking which not only results in separating one element from another but also in arranging them in terms of an implied hierarchy which renders the one element as subordinate to the other. This hierarchal structure and the perspective that the weaker element is passive, uncivilised, colonised and female will serve as the crux of disenchantment in the community and the legal culture for the purposes of this essay. Disenchantment itself can be understood as symptomatic of a masculine tradition.
Keywords: transformative constitutionalism; imagination; disenchantment; feminist